Sewage sludge pyrolysis and gasification for biochar production in circular economy - Anastasia Katsoulea; Antigoni Zafeirakou (Sustainable Futures)
For the past few decades, following circular economy principles, materials once considered waste are now examined as potential resources. This study seeks to depict the research that has been accomplished not only in the area of sewage sludge valorization through energy-producing technologies, but also the utilization of the derived by-products, such as biochar. A comprehensive bibliometric and visual analysis was conducted using VOSviewer software to examine research trends in sewage sludge pyrolysis and gasification for energy and biochar production, based on two advanced searches in the Scopus database.A general statistical analysis of the results was performed and graphs on various key parameters were generated. The temporal distribution of publications indicates growing interest in sewage sludge pyrolysis, gasification and their produced biochar over the past decade. Country-level analysis revealed that China is the predominant contributor in both research areas, underscoring its leading role in advancing sludge treatment and valorization technologies. The visual analysis further elucidated research trends and networks through co-occurrence and co-authorship mapping.This work represents the first bibliometric analysis to compare both sewage sludge pyrolysis and gasification in the context of biochar production, providing new insights into research disparities for each process. The results indicate that pyrolysis and its biochar have been extensively studied, whereas gasification remains relatively underexplored. The lower publication volume and citation rates suggest that gasification technologies and the potential applications of its biochar are still emerging. However, the upward trend in publications signals growing interest in this field, highlighting its potential for future development.